Coverage rates against vaccine-preventable diseases among healthcare workers in Sicily (Italy). (1st October 2020) - Ledda, Caterina; Rapisarda, Venerando; Maltezou, Helena C; Contrino, Eleonora; Conforto, Arianna; Maida, Carmelo Massimo; Tramuto, Fabio; Vitale, Francesco; Costantino, Claudio
Abstract: Background: Vaccination of healthcare workers (HCWs) reduces the risk of occupational vaccine-preventable diseases (VPDs), prevents their nosocomial transmission and preserves healthcare delivery during outbreaks. Extensive implementation of vaccination programmes for HCWs allowed the elimination or control of several VPDs within healthcare facilities; despite these, the vaccine adherence rates among HCWs are persistently suboptimal. Methods: A questionnaire was self-administered by HCWs to assess their vaccination rates against several VPDs and self-reported immunity in two university hospitals of Southern Italy (Catania and Palermo). Results: A total of 2586 questionnaires were analysed. More than 50% of HCWs did not know their own immunization status against diphtheria, tetanus and pertussis. More than half of the HCWs interviewed at University Hospital (UH) of Catania (UHC) was immune against measles (72.1%), in contrast with data reported at the UH of Palermo (UHP) (45.9%). Immunization status against mumps (67.5% UHC vs. 40.6% UHP), rubella (69.9% UHC vs. 46.6% UHP) and varicella (70.4% UHC vs. 50.7% UHP). Overall, about 30% of HCWs did not know their own immunization status against these VPDs. Moreover, 84.2% at UHC and 66.7% at UHP stated that was previously vaccinated against hepatitis B. Conclusion: Vaccination coverage rates reported from the HCWs against influenza during the last three seasons were considerably low. In conclusion, totally inadequate vaccination rates against several VPDs were found in two university hospitals in Sicily, in terms of preventing not only disease transmission by susceptible HCWs, but also nosocomial outbreaks, confirming data from previous national and international studies.